Comorbidity and risk of cardiac events in patients with acute coronary syndrome - R.R. Komorovsky (Кардіохірургія та інтервенційна кардіологія)
The aim – to assess the prevalence of comorbidities in patients with acute coronary syndrome and to evaluate the effect of simplified comorbidity index (SCI) on outcomes of patients undergoing different treatment strategies. Materials and methods. Prospective follow-up was performed in 337 patients with acute coronary syndrome. Comorbid conditions were recorded and SCI was calculated. The main outcomes were cardiac death and myocardial infarction. Results. A total of 150 (45 %) patients were found to have comorbidities. The rate of cardiac events was increasing progressively as the SCI value increased, from 4.3 % in SCI = 0 to 12.3 % in SCI = 1–2 (hazard ratio 3.05, 95 % confidence interval 1.37–7.45; р = 0.009) and to 21 % in SCI ≥ 3 (hazard ratio 6.54, 95 % confidence interval 6.32–20.40; р = 0.0007). The greatest differences between patients of different comorbiditity categories were observed after 20 months of follow-up. In the subgroup of revascularized patients no significant differences were observed in terms of survival and cardiac event rates between patients of different comorbidity categories. Conclusions. A simplified comorbidity index may be used for risk stratification of patients with acute coronary syndrome. Invasive treatment strategy may decrease the risk of cardiac adverse events and improve long-term prognosis of patients with comorbidities.